Temporal and abiotic fluctuations may be preventing successful rehabilitation of soil‐stabilizing biocrust communities. Issue 5 (12th June 2019) - Young, Kristina E.; Bowker, Matthew A.; Reed, Sasha C.; Duniway, Michael C.; Belnap, Jayne
Abstract: Land degradation is a persistent ecological problem in many arid and semiarid systems globally (drylands hereafter). Most instances of dryland degradation include some form of soil disturbance and/or soil erosion, which can hinder vegetation establishment and reduce ecosystem productivity. To combat soil erosion, researchers have identified a need for rehabilitation of biological soil crusts (biocrusts), a globally relevant community of organisms aggregating the soil surface and building soil fertility. Here, the impact of plant and biocrust cover was tested on soil erosion potential in the piñon – juniper woodlands of Bandelier National Monument, New Mexico, USA. Biocrusts were found to be similarly influential to vascular plants in reducing erosion, largely acting by promoting surface roughness. The potential to rehabilitate biocrusts within the Monument was also tested. Plots were inoculated on eroding soils before the summer monsoon with greenhouse‐cultured biocrusts. In a full‐factorial design, treatments to reduce or halt erosion were administered to the inoculated plots and their paired controls. These erosion‐reduction treatments included barriers to overland flow (flashing), slash placement, and seeding of vascular plants. Dynamic changes to soil stability, penetration resistance, and extractable soil nutrients were observed through time, but no strong effects with the addition of biocrust inoculum, seeding, or erosion intervention treatments were seen. The results do suggest possible ways forward to successfully rehabilitate biocrust, including varying the timing of biocrust application, amending inoculum application with different types of soil stabilization techniques, and adding nutrients to soils. The insights gleaned from the lack of response brings us closer to developing effective techniques to arrest soil loss in these socially and ecologically important dryland systems.